2018
DOI: 10.1016/j.mri.2018.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Rapid B1 field mapping at 3 T using the 180° signal null method with extended flip angle

Abstract: The EA-NSM permits accurate, fast, and practical B mapping in a 3 T clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Figure2shows examples of derived T 1 and APD maps obtained from the phantom imaging data using FAM. As expected, the ζ map exhibits a smooth decrease in ζ as a function of distance from the center of the phantom, in accordance with previous observations[39][40][41]. More importantly, derived T 1 and APD maps with ζ correction exhibit homogeneity across the phantom, reflecting the homogeneity of the phantom itself.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…Figure2shows examples of derived T 1 and APD maps obtained from the phantom imaging data using FAM. As expected, the ζ map exhibits a smooth decrease in ζ as a function of distance from the center of the phantom, in accordance with previous observations[39][40][41]. More importantly, derived T 1 and APD maps with ζ correction exhibit homogeneity across the phantom, reflecting the homogeneity of the phantom itself.…”
supporting
confidence: 90%
“…Assuming a longitudinal steady-state has been reached, the magnitude of the SPGR signal is conventionally given by the Ernst equation through S SPGR (ζθ, TR) = APDsin(ζθ) 1 − exp −TR/T 1 / 1 − exp −TR/T 1 cos(ζθ) [1] where the dimensionless quantity ζ denotes the local, voxel-wise, B 1 + scaling factor, APD is the apparent proton density representing the signal amplitude and is proportional to the true PD, reception field amplitude B [33,[38][39][40][41][42][43][44], only modest spatial resolution imaging is required.…”
Section: Four-angle Methods (Fam)mentioning
confidence: 99%
“…The same threshold value was successfully used to improve myelin water fraction (MWF) mapping from MSE imaging datasets (Bouhrara et al, 2017b; Bouhrara et al, 2018b). Of note, as both B1 and noise SD vary smoothly throughout the images (Aja-Fernández and Vegas-Sánchez-Ferrero, 2016; Bouhrara and Bonny, 2012; Bouhrara and Spencer, 2016; Rejimon et al, 2018), we found that a neighborhood of R = 15 mm x 15 mm x 15 mm provided excellent results through a range of spatial resolution, SNR, and CBF values.…”
Section: Discussionmentioning
confidence: 68%
“…d ( i,j ) between i and each candidate voxel j belonging to W is calculated and arranged in ascending order, with the R voxels having the smallest distance being incorporated into the MLE of its true intensity through trueA^k(i) = argmaxAk{i=1RlogSk(i)σ2iRSk2(i)+Ak22σ2+i=1Rlog I0[Sk(i) Akσ2]}. where trueA^k(i) is the estimated true intensity of spectral image k and index voxel i . The size of the window W must be sufficiently large to ensure inclusion of an adequate number of similar voxels, and sufficiently restricted to ensure that the transmission and reception B 1 fields is approximately constant within the window (25, 26).…”
Section: Theorymentioning
confidence: 99%